2004
DOI: 10.4049/jimmunol.173.5.3337
|View full text |Cite
|
Sign up to set email alerts
|

Intracellularly Expressed TLR2s and TLR4s Contribution to an Immunosilent Environment at the Ocular Mucosal Epithelium

Abstract: Epithelial cells are key players in the first line of defense offered by the mucosal immune system against invading pathogens. In the present study we sought to determine whether human corneal epithelial cells expressing Toll-like receptors (TLRs) function as pattern-recognition receptors in the innate immune system and, if so, whether these TLRs act as a first line of defense in ocular mucosal immunity. Incubation of human primary corneal epithelial cells and the human corneal epithelial cell line (HCE-T) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 39 publications
14
130
1
3
Order By: Relevance
“…65,66 The response of human corneal epithelial cells to stimulation by model toxigenic or non-toxigenic S. aureus was also strikingly similar to that of human vaginal epithelial cells exposed to an Since TLR-based recognition of Gram positive bacteria is a main sensing mechanism of mammalian cells, 18 we tested whether induction of CCL20 expression by HCECs and their primary cell counterparts is dependent on TLR2 or NOD2 as might be predicted. The observation that agonists of these receptors did not effect CCL20 expression by these cells would be consistent with the previous observation that little TLR2 occurs on the surface of the human cornea normally, 24 suggesting that S. aureus is sensed by these cells via another pathway. It was previously noted that protein A, which is expressed by S. aureus early in log phase, 43 is capable of stimulating TNFα and IL8 expression by corneal epithelial cells in a TLR2 independent fashion, 44 supporting this prospect.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…65,66 The response of human corneal epithelial cells to stimulation by model toxigenic or non-toxigenic S. aureus was also strikingly similar to that of human vaginal epithelial cells exposed to an Since TLR-based recognition of Gram positive bacteria is a main sensing mechanism of mammalian cells, 18 we tested whether induction of CCL20 expression by HCECs and their primary cell counterparts is dependent on TLR2 or NOD2 as might be predicted. The observation that agonists of these receptors did not effect CCL20 expression by these cells would be consistent with the previous observation that little TLR2 occurs on the surface of the human cornea normally, 24 suggesting that S. aureus is sensed by these cells via another pathway. It was previously noted that protein A, which is expressed by S. aureus early in log phase, 43 is capable of stimulating TNFα and IL8 expression by corneal epithelial cells in a TLR2 independent fashion, 44 supporting this prospect.…”
supporting
confidence: 91%
“…22,23 Direct examination of primary human corneal epithelial cells, however, revealed little, if any, TLR2 on the surface, and showed instead the existence of readily detectable pools of intracellular TLR2 of unknown function or consequence. 24 It was therefore of interest to examine the response of corneal epithelial cells to S. aureus exposure, and to compare this response with the findings of others using epithelial cells from non-immune privileged tissues to detect possible immune priviliged tissue specific response programs. Since pore forming toxins Staphylococcus aureus is a leading cause of invasive infection.…”
Section: Response Of Corneal Epithelial Cells To Staphylococcus Aureusmentioning
confidence: 99%
“…But given our recent uterine epithelial cell findings, we cannot exclude the possibility that there are other immunological parameters that we have not measured and that the Fallopian tube may actually be responding to PAMPs other than poly(I:C) Another possibility might be that the TLR2 and 4 expression that we have detected is intracellular and therefore responsive to intracellular pathogen invasion such as N. gonorrheoe and Chlamydia that are pathogens of the upper FRT. Intracellular expression been shown by Ueta et al (80) in corneal epithelial cells where TLR 2 and 4 were expressed but did not respond to agonists resulting in an immuno-silent environment at the ocular mucosa. Alternatively, if expression of TLR 2 and 4 is exclusively at the cell surface, upregulation of TLR, rather than evoking the release of proinflammatory mediators, might induce signaling inhibitors such as Tollip, IRAK-M, and SOCS-1 (which we have not measured in this study) to promote PAMP tolerance as a mechanism to prevent immune activation.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, despite no significant change in total protein expression of TLR4 with β 2 -AR stimulation, confocal microscopy revealed redistribution of the TLR4/CD14 complex ( Figure 3B). A previous study showed that human corneal epithelial cells express TLR2 and TLR4 intracellularly but not at the cell surface and fails to respond to LPS even on artificial translocation of LPS [18] . Thus, membrane-bound TLRs play a central role in LPS-induced inflammatory response, and β 2 -AR mediated reduction of membrane-bound TLRs was responsible for the reduced inflammatory response in monocytes.…”
Section: Wwwchinapharcom Wang W Et Almentioning
confidence: 98%